Treasure hunt - Barbo, Maria S.; Del Sur, Duendes; Cartoon Network (Television network) (New York, NY : Scholastic, 2002)
Scooby and the gang have a picnic and look for treasure.
At head of title: Cartoon Network.
Twenty-four flash cards included at back of book.